PENGEMBANGAN BUKU DIGITAL CERITA BERGAMBAR BERBENTUK FLIPBOOK DALAM PEMBELAJARAN TEMATIK SISWA KELAS V - Melly Monica; Siti Halidjah; Rio Pranata (Universitas Hamzanwadi, 2022)
This study aims to describe the steps of developing a digital picture book in the form of a flipbook that is valid and practical in thematic learning for fifth grade students at 39 Pontianak City Elementary School. This study uses the Research and Development (R&D) method based on the ADDIE model which consists of five development steps, namely Analysis, Design, Development, Implementation and Evaluation. The data sources of this research are design experts, material experts and students validators. The results of the validation of design experts and materials experts obtained an average of 5